2014
DOI: 10.1007/s11751-014-0206-y
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant treatment of chronic osteomyelitis of the tibia following exogenous trauma using OSTEOSET®-T: a review of 21 patients in a regional trauma centre

Abstract: Surgical debridement and prolonged systemic antibiotic therapy are an established management strategy for infection after tibial fractures. Local antibiotic delivery via cement beads has shown improved outcome but requires further surgery for extraction of beads. OSTEOSET®-T is a resorbable bone void filler composed of calcium sulphate and 4 % tobramycin that is packed easily into bone defects. This is a review of the outcomes of 21 patients treated with OSTEOSET®-T for osteomyelitis of the tibia. This is a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 14 publications
1
32
3
Order By: Relevance
“…Second, incidence of the adverse events apart from infection relapse was 12/34, with aseptic wound leakage being the most frequently observed. Previous studies reported that the proportion of aseptic wound leakage ranged from 6/100 (McNally et al 2016) to 7/21 (Humm et al 2014), showing an average incidence of 16% (Ferguson et al 2017), whereas, it was 11/34 in our patients, higher than most of the previous studies. The difference may be primarily attributed to 2 reasons.…”
Section: Discussioncontrasting
confidence: 86%
“…Second, incidence of the adverse events apart from infection relapse was 12/34, with aseptic wound leakage being the most frequently observed. Previous studies reported that the proportion of aseptic wound leakage ranged from 6/100 (McNally et al 2016) to 7/21 (Humm et al 2014), showing an average incidence of 16% (Ferguson et al 2017), whereas, it was 11/34 in our patients, higher than most of the previous studies. The difference may be primarily attributed to 2 reasons.…”
Section: Discussioncontrasting
confidence: 86%
“…The CaP@MSi and DOX-CaP@MSi were used in ratio of 38 and 12 wt%, respectively. The 12 wt% of DOX-CaP@MSi in the formulation corresponded to the 2 wt% content of drug similar to drug content in commercially available spherical granules (0.5-5 wt%) [21,22]. The microcrystalline cellulose (MCC; Avicel PH 101, Sigma-Aldrich) and ethyl cellulose (EC; Ethocel 20 cP, Dow Chemical) were used as the excipients (45 and 5 wt%, respectively).…”
Section: Formulation Of Drug Delivery Systemsmentioning
confidence: 99%
“…This has been implicated in causing some local wound issues, with serous ooze in a proportion of cases 16,20,22, although this seems to be self-limiting 21.…”
Section: Calcium Sulphatementioning
confidence: 99%